Peran Terapi Farmakologi dan Non-Farmakologi dalam Pengelolaan Dry Eye Disease - Sitanggang, Grety; Himayani, Rani; Iyos, Rekha Nova; Mutiara, Hanna (CV. Jasa Sukses Abadi, 2024)
Dry Eye Disease (DED) is a multifactorial disorder of the ocular surface characterized by tear system imbalance, inflammation, and tissue damage, often leading to discomfort, visual disturbances, and a decline in quality of life. Managing DED requires a holistic approach that integrates both pharmacological and non-pharmacological therapies to alleviate symptoms while addressing underlying causes. Pharmacological treatments, such as artificial tears, anti-inflammatory agents (corticosteroids and cyclosporine), diquafosol tetrasodium, and oral pilocarpine, aim to restore ocular surface homeostasis. Non pharmacological approaches, including punctal plugs, lifestyle modifications, intense pulsed light (IPL) therapy, and nutritional supplementation with vitamin D and omega-3, are increasingly recognized for their supportive role in treatment. A comprehensive understanding of these therapeutic strategies is expected to improve DED management, enhance patients' quality of life, and prevent further complications.